Retrospective analysis of vitreoretinal surgery outcomes in diabetic retinopathy - A. P. Goydin (Российский офтальмологический журнал, 2022)
Purpose. To analyze the clinical and functional results of vitreoretinal operations in patients with type II diabetes mellitus and diabetic retinopathy (DR).Materials and methods. A retrospective analysis of vitreoretinal surgery outcomes in DR was performed in 421 patients (421 eyes), with type II diabetes mellitus and DR, with no previous history of retinal laser coagulation. The follow-up period was at least 4 years. Patients were divided into two groups depending on the postoperative course of the disease. Group I included 338 patients (338 eyes) with a single vitreoretinal intervention followed by stabilization of the pathological changes over the whole follow-up period. Group II consisted of 83 patients (83 eyes), ca. 20 % of the cohort, with repeated vitreoretinal operations required by DR progression. In addition, the groups were analyzed according to the best corrected visual acuity (BCVA).Results. The initial BCVA of less than 0.1 was noted in 69 % of cases in Group I with a single surgery while that in Group II claimed 80.7 % of cases. By the 6th month, BCVA values revealed an average increase from 0.05 to 0.20 in Group I and an average increase from 0.05 to 0.08 in group II. In Group I, at the end of the follow-up the mean BCVA remained stable and was higher than before the operation, while in Group II it dropped and remained significantly lower than in Group I. Also, by the end of the follow-up the patients given a single vitreoretinal intervention whose BCVA was below 0.1 showed an increase in the mean BCVA value, whilst those with initial BCVA of 0.4–0.6 showed BCVA stabilization. Patients with repeated operations and initial BCVA below 0.1 showed no noticeable BCVA changes but those with BCVA 0.1–0.6 revealed a drop.Conclusions. Modern technologies of vitreoretinal surgery of severe DR stages ensure a stable anatomical outcome following a single surgery in 80 % of cases, a stable functional result in 59 % of cases. In 20 % of cases, relapses and the need for repeated operations are associated with the initially more pronounced diabetic alterations of the retina, probably due to the patients’ late referral. Timely detection of DR and referral of such patients to a specialized ophthalmology center is a necessary task.